2015
DOI: 10.1007/s00408-015-9804-9
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation as Possible Mediator for the Relationship Between Lung and Arterial Function

Abstract: Reduced lung function was associated with increased inflammation and arterial stiffness. The lack of association between arterial stiffness and inflammatory markers suggests that inflammation may not be the mediating link between lung and vascular function in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 63 publications
3
10
0
Order By: Relevance
“…We suggest that a reduction in either FEV 1 or FVC and an increase in IL-6 is so closely correlated that the inclusion of IL-6 into our multivariate Cox regression model eliminated the association between FVC and CV risk. We have previously shown a highly significant inverse association between IL-6 and both FEV 1 and FVC (both P < 0Á001) in this population [34]. This finding supports previous studies that showed a stronger relationship between IL-6 and lung function, when compared to other inflammation markers such as CRP and TNF-ɑ [35].…”
Section: Discussionsupporting
confidence: 89%
“…We suggest that a reduction in either FEV 1 or FVC and an increase in IL-6 is so closely correlated that the inclusion of IL-6 into our multivariate Cox regression model eliminated the association between FVC and CV risk. We have previously shown a highly significant inverse association between IL-6 and both FEV 1 and FVC (both P < 0Á001) in this population [34]. This finding supports previous studies that showed a stronger relationship between IL-6 and lung function, when compared to other inflammation markers such as CRP and TNF-ɑ [35].…”
Section: Discussionsupporting
confidence: 89%
“…Inflammatory mediators and cytokines produced by tumors or a host's innate response can exert immunomodulatory effects through apoptosis inhibition, DNA damage, and angiogenesis promotion [15]. Moreover, recent data showed that elevated SIR may contribute to impaired pulmonary function not only in patients with pulmonary disease and smokers but also in healthy individuals and non-smokers [11, 12, 16, 17]. The systemic effects of cancer-related inflammation can be quantified using routinely available serum SIR biomarkers, such as NLR, PLR, and LMR.…”
Section: Discussionmentioning
confidence: 99%
“…Possible mechanisms include inflammation, as arterial stiffness is markedly increased in patients with chronic obstructive pulmonary disease (COPD), a condition characterized by airflow obstruction and inflammation [1517]. While systemic inflammation, weight, smoking history, hypercholesterolemia, hypertension and diabetes have all been implicated, they do not fully account for the relationship between pulmonary function and arterial stiffness, suggesting that other factors could be involved [9, 13, 18].…”
Section: Introductionmentioning
confidence: 99%